Systematic Literature Review (SLR): Development of Online Market Corner Learning Media for Fifth Grade Elementary School Students - Nasrul Latifah; Waspodo Tjipto Subroto; Budi Purwoko (Elementary Teacher Education Program, Majalengka University, 2023)
The aim of this research is to describe the use of Canva to design advertisements that will be marketed via social media in a learning context. The method used in this research uses a qualitative approach with a Systematic Literature Review (SLR) review, with five steps used from the seven existing steps, namely (1) Asking research questions; (2) Finding studies; (3) Critical evaluation of the study; (4) Data collection; and (5) Data analysis and reporting. Based on the study that the researchers have conducted, it is concluded that the use of Canva has a very important role for its users, so that Canva will be ideally needed as an alternative learning media for students so that they have sufficient creativity in designing advertisements that will be promoted via social media in science learning context.